2019
DOI: 10.1155/2019/4203137
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Vibration Response Law of Multistory Building under Tunnel Blasting Loads

Abstract: This paper takes the Dizong tunnel engineering as its background. Combined with the on-site monitoring data, the wavelet packet program based on MATLAB was compiled to study the vibration response of the four-story masonry building in a typical southwestern mountainous area of China under the blasting load. The results showed that the maximum particle velocity increased to the 3rd floor and attenuation occurred on the 4th floor. The particle velocity in the z-direction was the largest and should be paid attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It can be seen from Table 7 that the PPV of field monitoring is consistent with that of numerical simulation, and the error is approximately 5%. e PPV obtained by numerical simulation is slightly larger than the PPV of on- Advances in Civil Engineering [10][11][12], even if under the same surrounding rock grade, the attenuation rate of PPV will vary because of the different degrees of blasting disturbance. If Sadov's empirical formula is used to regress the PPV of the surrounding rock conditions, then the correlation coefficient of regression will be low, and the regression results cannot ensure that the PPV will be controlled within a reasonable range.…”
Section: Analysis Of the Monitoring Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…It can be seen from Table 7 that the PPV of field monitoring is consistent with that of numerical simulation, and the error is approximately 5%. e PPV obtained by numerical simulation is slightly larger than the PPV of on- Advances in Civil Engineering [10][11][12], even if under the same surrounding rock grade, the attenuation rate of PPV will vary because of the different degrees of blasting disturbance. If Sadov's empirical formula is used to regress the PPV of the surrounding rock conditions, then the correlation coefficient of regression will be low, and the regression results cannot ensure that the PPV will be controlled within a reasonable range.…”
Section: Analysis Of the Monitoring Resultsmentioning
confidence: 78%
“…Xu et al [10] carried out field tests and numerical simulation to study the relationships between the blasting vibration velocity and the frequency over time, horizontal distance, and depth, and the stress distribution of the surrounding rock mass. Duan et al [11] and Huo et al [12] investigated the vibration velocity and vibration frequency of the existing structure and proposed a guideline for the blast safety zone based on vibration velocity, main frequency, and explosive quantity. Duan et al [13] studied the stress distribution of the surrounding rock and the propagation mode of the stress wave during blasting.…”
Section: Introductionmentioning
confidence: 99%
“…When the blasting stress wave propagates through the rock and soil to the building, it will cause vibration [27,28]. A large amount of literature indicates that the blasting vibration speed plays an essential role in blasting earthquake damage to the building [29], and the effect is continuous. Therefore, the attenuation law of blasting vibration velocity on buildings has been studied [30].…”
Section: Analysis Of Monitoring Results Of High-rise Buildingsmentioning
confidence: 99%
“…By monitoring the blasting test area, it can be found that the vibration velocity is between 1.2 and 1.4 cm/s while the blasting distance is between 65 and 70 m. According to the "GB 6722-2014 Safety Regulations for Blasting" and considering that the blasting seismic wave will produce amplification effect on the second and third floors of the building [33,34], it is determined that the maximum allowable vibration velocity is 1.2 cm/s. So the vibration velocity of the test area has not met the specifications.…”
Section: Problems With the Blasting Schemementioning
confidence: 99%